(untitled) (International journal of artificial intelligence, 2025)
This paper delves into the role of proper nouns in phraseological units (idioms), metaphors, and expressions, analyzing how these elements transcend their basic reference function and evoke deep cultural, historical, and symbolic connotations. By focusing on examples from English, Russian, and Uzbek, the study illustrates how personal names embedded in idioms not only represent individuals but also convey broader societal meanings, collective memories, and values. The research underscores how proper nouns in idiomatic expressions act as powerful symbols, cultural markers, and conveyors of moral messages, offering insights into the intersection of language, culture, and collective memory.